Desain Primer Gen Virulensi invA untuk Identifikasi dan Sekuensing Salmonella pada Sampel Karkas Ayam - R. P. Melati; S. Nurjanah; W. P. Rahayu (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2022)
Identification and sequencing of Salmonella require a specific primer as well as a virulence marker. Invasion gene (invA) is a gene found in all types of Salmonella, specific to Salmonella, and has a low mutation rate so that it can be used as a target gene for Salmonella identification. This study aimed to design a primer of invA gene of Salmonella spp. with long amplicons, has broad serovar coverage, and get an optimum PCR condition. Primers were designed and checked its specificity in silico using Primer-BLAST and then selected. Selected primer was evaluated for annealing temperature and primer concentration. Based on the sequential selection, it was obtained a set of invA gene primer with forwarding sequences GCCGGTGAAATTATCGCCAC (started at base 297) and reverses sequences CTCGTAATTCGCCGCCATTG (started at base 1763). Based on Primer-BLAST analysis, the primer gave an amplicon size of 1486 bp, has annealing temperature of 58 °C, capable of detecting at least 110 Salmonella serovars, capable to detect Salmonella contamination in chickens, and unable to detect the presence of Klebsiella sp., Citrobacter sp., Serratia sp., Hafnia sp., and E. coli. This primer can detect Salmonella very well with annealing temperature of 58 oC and primer concentration of 1.2 µM.